Preparation method of cerium oxide composite yttrium oxide material with porous sphere morphology

By using cerium oxide composite yttrium oxide material (pCeY) with porous spherical morphology as a catalyst, the problem of low removal efficiency of ROX and inorganic arsenic in the prior art was solved, efficient photocatalytic degradation and adsorption effects were achieved, and reaction efficiency was improved And maintains stability.

CN119386849APending Publication Date: 2025-02-07EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513705.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art faces the problems of long reaction time and low removal rate of inorganic arsenic when removing ROX and inorganic arsenic from water.

Method used

Using porous spherical morphology cerium oxide composite yttrium oxide material (pCeY) as a catalyst, the high specific surface area and abundant reaction sites of CeO2/Y2O3 composite materials are used to improve the light absorption efficiency and electron-hole Separation effect.

Benefits of technology

It achieves efficient degradation of ROX and effective removal of inorganic arsenic, improves photocatalytic efficiency, and maintains stable degradation activity under weak acid conditions, and has the potential for long-term application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386849A_ABST
    Figure CN119386849A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a cerium oxide composite yttrium oxide material with a porous sphere morphology. ROX in water can be efficiently removed, and the exposure risk of inorganic arsenic is reduced. CeO2 / Y2O3 composite materials with three morphologies of a block shape, a hollow sphere shape and a porous sphere shape are prepared through a hydrothermal method and are named as bCeY, hCeY and pCeY respectively, and performance testing is carried out. Results show that the porous spherical material pCeY can completely remove ROX within 70 minutes under simulated sunlight, and has relatively strong adsorption capacity on inorganic arsenic. Influences of factors such as morphology, dosage, ROX concentration, pH value, coexisting anions and humic acid of the catalyst on degradation and adsorption are researched and analyzed. Results show that the degradation activity of the system is high under the acidic condition, but part of inorganic anions inhibit the degradation effect. The catalyst has excellent stability, still maintains 100% degradation efficiency after four cycles, and has a low inorganic arsenic concentration all the time. The invention provides an efficient scheme for ROX removal and inorganic arsenic exposure control, and has practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a cerium oxide composite yttrium oxide material with a porous spherical morphology, which can be used to effectively remove ROX in water and improve ROX degradation in practical applications with a large amount of inorganic arsenic exposure. Background Art

[0002] Roxarsone (ROX) is a low-toxic organic arsenic that was once widely used as a livestock feed additive, mainly for preventing coccidiosis, improving feed utilization and promoting weight gain. Since the 1940s, ROX has been used in poultry and pig farming. However, ROX is difficult to be metabolized by animals, is almost completely excreted through feces, and has stable chemical properties. Thousands of tons of poultry manure are used as manure every year, causing organic arsenic to enter the soil and increase the arsenic content in the soil. After entering the soil, ROX is rapidly transformed through biological and non-biological processes, and its metabolites include DMA, HAPA, MMA, As(III) and As(V), among which As(III) is the most toxic, about 60 times that of As(V). Therefore, the conversion of As(III) to As(V) is an important detoxification process. Inorganic arsenic can be adsorbed and accumulated in the soil, which may cause arsenic pollution in soil and water, endangering human and environmental health. Although China, the European Union and the United States have banned the use of ROX, it is still used in countries such as India.

[0003] At present, the treatment methods of ROX mainly include adsorption, biodegradation, photolysis and advanced oxidation technology, especially the combination of advanced oxidation and adsorption, which can remove organic and inorganic arsenic at the same time. Advanced oxidation technology has attracted attention due to its high mineralization rate and high efficiency, but it faces the problems of long reaction time and low inorganic arsenic removal rate.

[0004] In order to solve these problems, the present invention uses cerium (Ce) as the core component of the catalyst. Cerium is a rare earth metal that is abundant, inexpensive and non-toxic. Due to its valence state transition between Ce (III) and Ce (IV), it exhibits excellent redox properties. Layered double hydroxide (LDH) materials have the advantages of easy synthesis, fixed metal ions, enhanced catalytic stability and cyclic capacity. Ce-based LDH has great potential in catalyst stability and advanced oxidation processes. Cerium oxide (CeO 2) is a semiconductor photocatalyst with a band gap of 2.6-3.4 eV. It has good photocatalytic activity, abundant oxygen vacancies and high oxygen ion conductivity, and is widely used in pollutant degradation. In addition, Ce-based catalysts such as cerium oxide and cerium hydroxide have strong adsorption capacity for arsenic. The morphology control of cerium oxide can improve the arsenic adsorption effect, and cerium hydroxide has a strong affinity for inorganic arsenic due to its abundant hydroxyl groups. During the adsorption process, cerium oxide removes inorganic arsenic by forming Ce-O-As bonds, and cerium hydroxide exhibits ultra-high arsenic adsorption capacity through Ce-As and Ce-O-As bonds. At the same time, Ce(IV) can oxidize toxic As(III) to less toxic As(IV), significantly reducing the toxicity of arsenic. Summary of the invention

[0005] The present invention provides a method for preparing a porous spherical cerium oxide composite yttrium oxide material, which can be used to effectively remove ROX in water and reduce the exposure to inorganic arsenic in practical applications. 2 / Y 2 O 3 The composite material (pCeY) is used as a catalyst in the degradation of ROX. The catalyst and the ROX solution are first placed in a dark environment to achieve adsorption equilibrium, and then the ROX degradation operation is carried out under simulated sunlight. The catalyst has a larger specific surface area, more reaction sites, and stronger visible light photoresponse ability, thereby improving the light absorption efficiency and the electron-hole separation effect. The system exhibits excellent photocatalytic degradation activity under weakly acidic conditions and has good stability.

[0006] Specifically, the present invention provides a method for preparing a cerium oxide composite yttrium oxide material with a porous spherical morphology, which can be used to effectively remove ROX in water and reduce the exposure to inorganic arsenic in practical applications. The method is as follows:

[0007] (1) A certain amount of Ce(NO 3 ) 3 and Y(NO 3 ) 3 Add to the mixed organic solvent and stir until completely dissolved;

[0008] (2) transferring the solution to an autoclave and maintaining it at a set temperature for a certain period of time;

[0009] (3) washing and drying the obtained material;

[0010] (4) The product is placed in a muffle furnace and kept warm according to set conditions to obtain a pCeY material.

[0011] Furthermore, the addition of Ce(NO 3 ) 3 The amount is 5-15 mmol, Y(NO3 ) 3 The amount is 3-7mM;

[0012] Further, the composition of the mixed organic solution used is 55-65 mL of isopropanol and 10-20 mL of glycerol;

[0013] Further, the stirring time of the solution is 25 to 35 minutes;

[0014] Further, the reaction temperature of the autoclave is 180-190°C, and the reaction time is 6-7 hours;

[0015] Furthermore, deionized water and anhydrous ethanol were used three times each when washing the material, and the drying temperature was 50-60°C;

[0016] Furthermore, the heating rate of the muffle furnace is 5-7°C / min, the temperature is raised to 500°C and kept at this temperature for 2-3 hours.

[0017] The obtained material is then used as a catalyst for degrading ROX. The catalyst and the ROX solution are first placed in a dark environment to reach adsorption equilibrium, and then the ROX degradation operation is performed under simulated sunlight. The ROX degradation method is as follows:

[0018] (1) Weigh a certain amount of catalyst into a quartz tube, and then add a certain concentration of ROX solution;

[0019] (2) Place in a dark environment for a certain period of time to achieve adsorption equilibrium;

[0020] (3) placing the quartz tube under sunlight simulated by a xenon lamp;

[0021] (4) Turn on the xenon lamp, take 1 mL of the solution at the set time point, and then filter it with a 0.22 μm filter.

[0022] Furthermore, the amount of the catalyst is 5-10 mg, the amount of the ROX solution is 40-50 mL, and the concentration is 10 mg / L.

[0023] Furthermore, the time to reach adsorption equilibrium in a dark environment is 25 to 30 minutes.

[0024] Furthermore, the sunlight is simulated by a 300W xenon lamp, and the xenon lamp head is equipped with an AM 1.5 filter.

[0025] The present invention proposes a method for preparing a cerium oxide composite yttrium oxide material with a porous spherical morphology, which can be used to effectively remove ROX in water and reduce the exposure of inorganic arsenic in practical applications. The first invention point is the design of a cerium oxide composite yttrium oxide material with a porous spherical morphology. The material has a large specific surface area and abundant reaction sites. By optimizing the morphology structure, the adsorption performance and photocatalytic activity of the catalyst are improved. The porous structure of the material gives it a stronger visible light response ability, effectively improves the light absorption efficiency, and reduces the recombination of electron-hole pairs, significantly improving the photocatalytic efficiency. The second invention point is the ability of the material to efficiently remove ROX and inorganic arsenic. The material can not only efficiently degrade ROX in water, but also effectively reduce the exposure of inorganic arsenic in practical applications, solving the problem of simultaneously removing organic and inorganic pollutants, and the catalyst has stable degradation activity in a weakly acidic environment, and maintains good stability during multiple cycles of use, with the potential for long-term application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 SEM image of pCeY

[0027] Figure 2 TEM image of pCeY

[0028] Figure 3 XRD pattern of pCeY

[0029] Figure 4 XPS full spectrum of pCeY (a) and high-resolution scans of Ce 3d (b), Y 3d (c), and O1s (d)

[0030] Figure 5 XPS spectra of pCe, including the full spectrum (a) and high-resolution scans of Ce 3d (b) and O1s (c); XPS spectra of pY, including the full spectrum (d) and high-resolution scans of Y 3d (e) and O1s (f)

[0031] Figure 6 (a) UV-visible diffuse reflectance spectra of bCeY, hCeY, pCeY, pCe and pY; (b) electrochemical impedance spectroscopy of bCeY, hCeY and pCeY; (c) photocurrent spectrum; (d) steady-state photoluminescence spectrum

[0032] Figure 7 Time-resolved fluorescence decay spectra of (a) bCeY, (b) hCeY, and (c) pCeY

[0033] Figure 8 Time-resolved fluorescence decay lifetimes of different samples

[0034] Fig. 9Effects of different catalyst systems on ROX degradation (a) and inorganic arsenic removal (b)

[0035] Fig.10 Effect of initial pH on ROX degradation (a) and inorganic arsenic adsorption (b); (c) Effect of inorganic anions and humic acid on ROX degradation

[0036] Fig.11 (a) Effects of different quenchers on ROX degradation; (b) EPR spectra of ·OH capture experiments in different systems, (c) ·O 2 - Capture experiment EPR spectrum, (d) 1 O 2 Capture experimental EPR spectra

[0037] Fig.12 (a) Reusability of pCeY for ROX degradation and total arsenic removal; (b) XRD spectra of pCeY before and after reaction Example

[0038] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples within the scope not exceeding the gist of the present invention.

[0039] Example 1

[0040] (1) pCeY

[0041] 10 mmol of Ce(NO 3 ) 3 and 5 mM Y(NO 3 ) 3 Add to a mixed organic solvent (60 mL isopropanol + 15 mL glycerol), stir for 30 min and completely dissolve, transfer the solution to a Teflon stainless steel autoclave and keep it at 180 ° C for 6 h. The obtained material was washed three times with deionized water and anhydrous ethanol, respectively, and dried at 60 ° C. The obtained product was heated to 500 ° C at a rate of 5 ° C / min in a muffle furnace and kept warm for 2 h to obtain porous spherical CeO 2 / Y 2 O 3 The composite material was named pCeY.

[0042] Comparative Example 1

[0043] (2)bC

[0044] 10 mmol of Ce(NO 3 ) 3 and 5 mM Y(NO 3 ) 3Add to 50mL of deionized water and stir for 2h to obtain a uniform transparent solution. Add 0.5M NaOH solution to the solution until its pH reaches 10.5. Stir the mixed solution continuously. After completion, put the mixed solution into a Teflon stainless steel autoclave and keep it at 150℃ for 10h. The obtained product is centrifuged and washed three times with deionized water and anhydrous ethanol respectively. The obtained product is heated to 500℃ at a rate of 5℃ / min in a muffle furnace and kept warm for 2h to obtain bulk CeO 2 / Y 2 O 3 The composite material was named bCeY.

[0045] Comparative Example 2

[0046] (3)hCeY

[0047] 10 mmol of Ce(NO 3 ) 3 and 5 mM Y(NO 3 ) 3 Add to a mixed organic solvent (60mL isopropanol + 15mL glycerol), stir for 30min and dissolve completely, transfer the solution to a Teflon stainless steel autoclave and keep it at 180°C for 6h. Wash the obtained material three times with deionized water and anhydrous ethanol respectively, and dry it at 60°C. Weigh 0.5g of the material again, dissolve it in 80mL deionized water, put it into a hydrothermal autoclave and keep it at 160°C for 3h, wash it three times with deionized water and dry it. The obtained product is heated to 500°C at a rate of 5°C / min in a muffle furnace and kept warm for 2h to obtain hollow sphere CeO 2 / Y 2 O 3 The composite material was named hCeY.

[0048] Experiments and data

[0049] 1. Catalyst photocatalytic performance test

[0050] bCeY, hCeY and pCeY were characterized by UV-Vis DRS, electrochemical impedance spectroscopy (ESI), photocurrent and steady-state photoluminescence (PL), respectively.

[0051] 2. ROX degradation and secondary adsorption of inorganic arsenic

[0052] The prepared materials were subjected to ROX degradation experiments under different systems to evaluate the effects of different catalysts and systems on ROX degradation and the adsorption of inorganic arsenic. Weigh 10 mg of catalyst into a quartz tube, and then add 50 mL of a 10 mg / L ROX solution. Place in a dark environment for 30 minutes to reach adsorption equilibrium. Place the quartz tube under the irradiation of a 300W xenon lamp, and install an AM 1.5 filter on the xenon lamp head. Turn on the xenon lamp, take 1 mL of solution at the set time point, and then filter it with a 0.22 μm filter head. 0.5 mL of the solution is used for liquid phase detection of ROX concentration, and the other 0.5 mL is used for inorganic arsenic detection.

[0053] 3. Study on the optimal conditions of the degradation system

[0054] Includes experiments on pH and anion effects.

[0055] (1) In the pH effect experiment, the initial pH of ROX was adjusted to the corresponding pH value by 0.1 mM NaOH and HCl, respectively, before the reaction. The other steps were the same as those in the degradation experiment.

[0056] (2) The ion effect experiment was conducted by adding 10 mmol / L NaCl and NaHCO 3 、NaNO 3 、Na 2 HPO 4 and HA, and the other steps were the same as those in the degradation experiment.

[0057] 4. Quenching experiment and degradation mechanism study

[0058] In order to understand the active oxygen species (ROS) involved in the pCeY / AM 1.5 photocatalytic degradation of ROX and their contributions, the present invention conducted a quenching experiment. Tert-butyl alcohol (TBA) was selected as the quencher of ·OH; p-benzoquinone (p-BQ) was selected as the quencher of ·O 2 - Furfuryl alcohol (FFA) and disodium ethylenediaminetetraacetate (EDTA-2Na) were selected as quenchers. 1 O 2 and h + The EPR experiment was used to further determine the ROS generated in the experiment and to infer the possible degradation mechanism.

[0059] 5. Cyclic stability test

[0060] After degradation-adsorption, the catalyst was collected by centrifugation and then added to 0.1M NaOH solution and stirred for 2h to desorb inorganic arsenic. The catalyst was then centrifuged to a neutral pH value. The catalyst in the centrifuge tube was then centrifuged together with the ROX solution and the next cycle experiment was continued.

[0061] Experimental Results

[0062] 1. Porous CeO 2 / Y 2 O 3 Successful preparation of composite materials

[0063] Figure 1 is the SEM image of pCeY, Figure 2 The TEM images show that pCeY is a monodisperse porous sphere with a smooth outer surface and a diameter of about 1 μm. In order to further illustrate the chemical structure of the catalyst, the catalyst was characterized by XRD. Figure 3 As shown in the XRD spectrum in Figure 2, pCe was detected near 28.6°, 33.16°, 47.10°, 56.48°, 59.12°, 69.21°, 76.57°, and 79.8°, which belong to octahedral CeO 2 The peaks of (PDF#78-0694) correspond to the (111), (200), (220), (311), (222), (400), (331) and (420) crystal planes. pY detected Y at 29.7°, 43.7° and 57.5° 2 O 3 The peak corresponding to Y 2 O 3 The (440), (134), and (622) crystal planes of pCeY (PDF#72-0927) were detected, which demonstrated the successful synthesis of pCeY.

[0064] XPS was used to further explain the valence and types of elements in pCeY. Figure 4 a indicates that the catalyst contains only four elements: C, O, Ce and Y, without any impurities being doped or generated. Figure 4 b is the high-resolution XPS spectrum of Ce 3d. The Ce 3d spectrum can be decomposed into four pairs of spin-orbit doublets (3d 3 / 2 and 3d 5 / 2): 882.52eV / 900.7eV, 888.75eV / 907.65eV, 898.07eV / 916.61eV and 885.41eV / 903.47eV. 882.52eV / 900.7eV, 888.75eV / 907.65eV and 898.07eV / 916.61eV correspond to the electronic states of Ce(IV), and 885.41eV / 903.47eV corresponds to the characteristic electronic states of Ce(III). Figure 4 c is the high-resolution XPS spectrum of Y 3d. The peak at 156.63 eV is Y 3d 5 / 2 , the peak at 158.57 eV is Y 3d 3 / 2 , both correspond to Y2 O 3 / Y(OH) 3 Species. Figure 4 d is the high-resolution XPS spectrum of O1s, where the peaks at 531.64 and 529.04 eV are attributed to lattice oxygen and adsorbed oxygen, respectively.

[0065] Figure 5 a and c prove the existence of C, O and Ce in pCe, and C, O and Y in pY. Figure 5 The Ce peak in b is compared with Figure 5 The Ce peak in b shifts to high field (0.3-0.5 eV). Figure 5 The Y peak in pCeY shifts to a lower field (0.4-0.6 eV). This indicates that electrons migrate from Ce to Y in pCeY. Figure 5 c and f also show that pCeY also shifts to the high field compared to O in pCe and pY, which indicates that O in pCeY also donates electrons to Y. The above results show that CeO 2 and Y 2 O 3 There is a strong interaction between them, and electrons can move from CeO 2 To Y 2 O 3 migrate.

[0066] 2. Photocatalytic performance of catalyst

[0067] The photocatalytic properties of composite materials with different morphologies were explored by comparing the spectra of three composite materials with different morphologies and pure pCe and pY. Figure 6 a is the spectrum of three composite materials with different morphologies and pure pCe and pY. All materials maintain high light absorption capacity in the range of 200-400nm. However, the light absorption capacity of pCe in the range of 400-600nm is significantly weaker, while pY appears dark black due to its porous spherical structure and can maintain strong light absorption capacity in the entire spectrum. The light absorption intensity of composite materials with different morphologies in the range of 400-600nm is pCeY>hCeY>bCeY. Therefore, the change in morphology improves the light absorption capacity of the catalyst in the wavelength range of 400-600nm, and the absorption edge is red-shifted. EIS is used to test the separation of photogenerated carriers of the catalyst. Figure 6 As shown in b, the arc radius of bCeY is the largest, and the arc radius of pCeY is the smallest. Therefore, it can be concluded that the porous sphere structure makes CeO 2 / Y 2 O 3 The electron-hole separation efficiency of the composite material was improved. The photocurrent was used to test the separation efficiency of the photogenerated electrons and holes of the catalyst. Figure 6c shows that when the morphology is hollow sphere, the photocurrent density increases slightly, while when the morphology is porous sphere, the photocurrent density of pCeY is greatly improved. This result shows that the porous morphology is beneficial to further promote the separation of electron-hole pairs. In the PL spectrum, Figure 6 d shows that the fluorescence intensity decreases with the change of morphology, and the electron-hole recombination rate decreases, among which the electron-hole recombination rate of pCeY is the lowest. The results of time-resolved fluorescence decay spectroscopy also prove this point ( Figure 7 ). The fluorescence decay of pCeY is slower than that of hCeY and bCeY. According to the data in 8, the average lifetime gradually increases from 0.133ns of bCeY to 0.191ns of pCeY, indicating that the electrons in pCeY have a longer fluorescence lifetime and can be transferred to the corresponding active sites to participate in the reaction. The above photoelectrochemical tests show that the porous sphere structure will maximize the light absorption capacity of the catalyst and the separation efficiency of photogenerated electrons and holes, which is beneficial to improve the activity of the photocatalytic reaction.

[0068] In the process of photocatalytic degradation, due to the conduction band ratio of pCeY E0(O 2 / ·O 2 - =-0.33 eV vs NHE) is more negative, so the photogenerated electrons in the conduction band of the catalyst can react with dissolved oxygen in the solution to generate O 2 - , and the positive shift of the conduction band potential of pCeY can promote the transfer of photogenerated electrons from the conduction band to dissolved oxygen, thereby generating ·O 2 - , which is ultimately converted into the main active species in this process 1 O 2 Therefore, pCeY has a stronger ability to photocatalytically degrade ROX than the first two catalysts.

[0069] 3. Degradation Experiment

[0070] In order to further demonstrate the superiority of pCeY material in the degradation of ROX and secondary adsorption of inorganic arsenic, the present invention compares it with two other materials with different morphologies, hCeY and bCeY. Fig. 9 As shown in a, with the change of morphology (from block to porous sphere), the degradation effect of the system becomes stronger and stronger. After 90 minutes of illumination with different materials, bCeY and hCeY degraded 65.0% and 93.2% of ROX, respectively, while pCeY achieved 100% ROX degradation effect at 70 minutes. In the non-illuminated system, after the adsorption was completed, the concentration of ROX hardly changed. These results show that the morphology of pCeY and illumination both play an important role in the degradation process. As for the adsorption of inorganic arsenic, the results are as follows Fig. 9b. The concentration of inorganic arsenic (CIA) in the dark environment is extremely low because almost no ROX is degraded. Under light, no inorganic arsenic appears in the whole process because CeO 2 / Y 2 O 3 The composite material has more inorganic arsenic adsorption sites, and the degraded ROX produces inorganic arsenic which is adsorbed in situ.

[0071] 4. Optimal conditions for degradation

[0072] In order to further illustrate the most suitable application conditions of the present invention, the optimal conditions were studied. First, the effect of the initial pH of the reaction on the degradation of ROX and the adsorption of inorganic arsenic was investigated. Fig.10 As shown in a. First, the pollutant solution with an initial pH of about 4.2 was adjusted to the corresponding pH using 0.1 mM NaOH and HCl solutions before the experiment was carried out. When the pH value was 3, the degradation effect of ROX was slightly inhibited, while when pH>7, the degradation effect of pCeY on ROX decreased significantly. The above results show that weakly acidic conditions are more conducive to the removal of ROX.

[0073] For the adsorption of inorganic arsenic, the results are as follows Fig.10 As shown in (b), under all pH conditions, CIA was kept in a relatively low range during the entire degradation process, but this does not mean that pCeY has good inorganic arsenic adsorption capacity under all pH conditions, because under higher pH conditions, ROX was hardly degraded, which is the real reason for the low CIA under alkaline conditions.

[0074] There are many impurities such as ions in natural water that may affect the degradation of ROX. In order to further illustrate the possible impact of natural water on the present invention, the effects of several inorganic anions and humic acid on the degradation of ROX are investigated here. The results are as follows: Fig.10 c. Add Cl - and NO 3 - After addition of HCO 3 2- and HPO 4 2- When the degradation is almost completely inhibited, according to Fig.10 The conclusion obtained in a is that the degradation effect will be greatly inhibited under weak alkaline conditions, which leads to HCO 3 2- and HPO 4 2- After addition, the degradation of ROX was inhibited. The addition of humic acid also led to the inhibition of ROX degradation.

[0075] 5. Quenching experiment and degradation mechanism

[0076] To further illustrate the active oxygen species (ROS) involved in the pCeY / AM1.5 photocatalytic degradation of ROX and their contribution, the present invention conducted a quenching experiment, and the results are shown in Fig.11 As shown in Figure 2, the addition of tert-butyl alcohol (TBA) as a quencher of ·OH resulted in almost no change in the degradation of ROX. 2 - The degradation rate of ROX was reduced from 100% to 63.8% by adding furfuryl alcohol (FFA) and disodium ethylenediaminetetraacetate (EDTA-2Na) as quenchers. 1 O 2 and h + The above results show that the role of O in the degradation of ROX is almost completely inhibited. 2 - , 1 O 2 and h + , among which the leading role is played by 1 O 2 and h + .

[0077] The ROS generated during the degradation process were further determined by EPR experiments. Fig.11 bd. First, Fig.11 As shown in b, in a reaction system with water as the solvent, 5,5-dimethyl-1-pyrroline N-oxide (DMPO) is used as a capture agent. After capturing OH, a peak with an intensity of 1:2:2:1 is detected, but Fig.11 In b, after adding pCeY, no obvious peak appeared, indicating that no ·OH was generated in the system. Methanol was used as a solvent to quench the ·OH in the system, and DMPO was used as a capture agent to detect the ·O in the presence or absence of pCeY under light. 2 - The production situation, Fig.11 There is still no obvious 2 - Finally, 4-amino-2,2,6,6-tetramethylpiperidine (TEMP) was used as a capture agent to detect the peaks in the reaction. 1 O 2 , Fig.11 There are three peaks with intensities of 1:1:1 in d. 1 O 2 Compared with the system without catalyst, the peak of 1 O2 The intensity of the peak is greatly enhanced, indicating that 1 O 2 of massive production.

[0078] 6. Cyclic stability test

[0079] In order to further illustrate the cyclic stability of pCeY on ROX degradation and inorganic arsenic adsorption, the present invention recovered pCeY by centrifugation and washing and conducted a cyclic stability test. Fig.12 As shown in a, in the first four cycles, the ROX degradation rate reached 100% after 90 minutes of illumination, which reflects the superiority of the pCeY cyclicity. However, in these four cycles, the concentration of inorganic arsenic gradually increased. In the first two cycles, the concentration of inorganic arsenic was very low. After the degradation was completed in the third cycle, the concentration of inorganic arsenic reached 0.195 mg / L. After the degradation was completed in the fourth cycle, the concentration of inorganic arsenic reached 0.412 mg / L. The catalyst after four cycles was washed with 0.1M NaOH to remove the inorganic arsenic adsorbed on the catalyst surface and release the inorganic arsenic adsorption sites on the catalyst surface. After washing with NaOH, the adsorption capacity of pCeY for inorganic arsenic was restored, and the solution still maintained an ultra-low concentration of inorganic arsenic throughout the process. The use of XRD to detect its crystal structure further proved the changes in pCeY after the reaction, and the results are shown in Fig.12 b. There is no obvious difference in the XRD peaks before and after the reaction. From the above results, it can be seen that pCeY has good ROX degradation ability and very good cycle stability. With the increase of the number of cycles, pCeY will gradually reach the adsorption capacity of inorganic arsenic, but after alkaline washing, the inorganic arsenic adsorption capacity of pCeY is restored.

[0080] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. The present invention relates to a method for preparing a cerium oxide composite yttrium oxide material with a porous spherical morphology, which is used to effectively remove ROX in water while reducing the exposure risk of inorganic arsenic in practical applications. The catalyst preparation method is as follows: (1) Add a certain amount of Ce(NO3)3 and Y(NO3)3 into a mixed organic solvent and stir until completely dissolved; (2) transferring the solution to an autoclave and maintaining it at a set temperature for a certain period of time; (3) washing and drying the obtained material; (4) The product is placed in a muffle furnace and kept warm according to set conditions to obtain a pCeY material.

2. The method according to claim 1, characterized in that The amount of Ce(NO3)3 added is 5-15 mmol, and the amount of Y(NO3)3 is 3-7 mM.

3. The method according to claim 1, characterized in that The composition of the mixed organic solution used is 55-65 mL of isopropanol and 10-20 mL of glycerol.

4. The method according to claim 1, characterized in that The stirring time of the solution is 25 to 35 minutes.

5. The method according to claim 1, characterized in that The reaction temperature of the autoclave is 180-190°C, and the reaction time is 6-7 hours.

6. The method according to claim 1, characterized in that When washing the material, deionized water and anhydrous ethanol were used three times each, and the drying temperature was 50-60°C.

7. The method according to claim 1, characterized in that The heating rate of the muffle furnace is 5-7°C / min, and the temperature is raised to 500°C and kept at this temperature for 2-3 hours.